PENGARUH BRAND IMAGE, KUALITAS PRODUK, PERSEPSI HARGA TERHADAP PEMBELIAN ULANG KOPIJANJI JIWA - Hanna Rusnovia (2023)
As one of the agricultural countries, Indonesia is more Lots rely on agriculture. One of the subsector to be rely on is the Coffee Sector. Coffee consumption in Indonesia is also increasing because supported by high coffee production . This is a Quantitative study aim for analyze influence of Brand Image, Product Quality, Price of Perception to Repurchase Decision Janji Jiwa's Coffee. Sample from this study is student Faculty of Economics and Business UPN Veteran Jakarta Class of 2019,2020,2021,2022 with amount sample as many as 100 people. The sampling technique was carried out with non-probability sampling with purposive sampling method . Data collection using a questionnaire and analysis done use application SmartPLS 3.0. Research results showing that : (1) Brand Image has No significant Influential to repurchase decision of 0.301, (2) Quality Product has No significant influential to repurchase decision of 0.209, (3) price perception has an effect positive and significant to repurchase decision of 0.375.